Tensions Between Policy and Practice in New Zealand Secondary School Appraisal: A Critical Analysis - Morgan, Gavin (Auckland University of Technology, 2017)
Annual appraisal of New Zealand’s state teachers has been a legislated requirement of Board of Trustees employers since 1997. Over the past 20 years, accountability mechanisms implemented to placate the manufactured public crisis about the state of education have, over time, shifted from the reassurance provided by local policy to the examination of individual teacher performance. Teacher appraisal itself is a complex performance management process with accountability and development requirements for both the teacher and the school, yet the hierarchical structures reinforced by neoliberal ideology and managerial practices have privileged accountability requirements over development opportunities. Instead of understanding appraisal in the dual terms of accountability and developmental or the exclusive terms suggested by either accountability or development, this thesis encourages school leaders to give greater attention to the importance of teacher development for accountability and leader accountability for development. This study focuses on the dichotomy between the espoused conditions of appraisal explained in school appraisal documentation with the experiences shared by 13 curriculum leaders across three South Auckland secondary schools. The research methodology combined case study design with critical theory and the philosophical hermeneutics of Hans-Georg Gadamer. Following a group interview with five curriculum leaders from one school and individual interviews with four leaders from the remaining two schools, participant narratives were written as a series of representative vignettes. The stories of these leaders were then synthesised to create a meta-narrative to challenge the reliance on top-down policy to determine teacher professionalism. This study uncovered four main findings. (1) To counter the myriad of accountabilities required by external agencies, the schools have aligned professional development and performance management systems. (2) Despite the illusion of systemic cohesion provided by this rational alignment, appraisal practices are fragmented and vary between departments. (3) Positioned between accountability mechanisms, professional development in the form of professional inquiries has generated a culture of evidence collection. Beneath the surface of espoused commitment to this development sits leader reticence to profess dissatisfaction with these artificial practices. (4) External accountability measures may enhance the appearance of professionalism, but greater responsivity to bottom-up practices grounded in collegiality and interdependence is needed if more professional understandings of accountability are to be realised.
Keywords: Teacher appraisal; Gadamer; Teacher accountability; Teacher development